Pelatihan Pembuatan Cendawan (Cendol Warna-Warni) berbasis pangan Lokal sebagai alternatif Wirausaha - Asnat C. Bani Bili; Yunita R.Bani Bili; Defrianty Kotta Kally (Jurnal Kelimutu Pengabdian Masyarakat, 2022)
The condition of Covid-19 Pandemic has been going on for two years and has greatly affected people's activities, especially their economic activities; because of that, a creative, innovative, and creative entrepreneur will have smart ideas to maintain his business while at the same time earning money. One of the appeals of the East Nusa Tenggara Provincial Government is for the people of East Nusa Tenggara to utilize local food as a food ingredient. In response to this condition, the Undana PKM Team carried out activities to innovate local food into Cendawan Ice (Colorful Cendol), as well as food for family consumption as well as an alternative to gain profit or income.